Limbah Penebangan Kayu di Perusahaan PT. Dwimajaya Utama - I Nyoman Surasana; Kristiani D Limbong; Yosep (Program Pascasarjana Universitas Palangka Raya dan (and) Ikatan Ahli Teknik Penyehatan dan Teknik Lingkungan Indonesia (IATPI), 2020)
This study aims to determine the volume of wood waste (in units of m3 and %) in IUPHHK-HA PT. Dwimajaya Utama. The research was carried out in cutting plots K-18 (RKT 2015) and felling plots J-21 (RKT 2016). As many as 8 units of sample plots measuring of 100 m x 100 m were purposively selected and then the waste resulted from 56 trees that had been felled were observed. The results showed that the woods potential on the cutting plot K-18 were 229.32 m3 while on plot J-21 were 200.03 m3, total volume of waste from the two cutting plots were 429.35 m3. Second, the reali-zation of logs production on the felling plot K-18 were 165.29 m3 (72.07%) and on plot J-21 were 145.73 m3 (72.86%) and the total from the two cutting plots were 311.02 m3 (72.44%). Thirdly, the mount of felling waste on felling plot K-18 were 64.05 m3 (27.93%) and on plot J-21 were 54.28 m3 (27.14%); resulting the total waste from both felling plots were 118.33 m3 ( 27.56%). Percentage of waste to production on felling plot K-18 were 38.75%, and on plot J-21 were 37.25%, and the mean from the two cutting plots were 38.00%. Forest potential structure for the two logging plots, namely timber potential around 429.35 m3, realized logs production of 311.02 m3 (72.44%) and resulted waste around 118.33 m3 (27.56%). The relatively low percentage of felling waste indicates that the application of RIL (Reduce Impact Logging) in logging activities is relatively successful.